Safety and durability of AGT103-T autologous T cell therapy for HIV infection in a Phase 1 trial - Muvarak, Nidal; Li, Haishan; Lahusen, Tyler; Galvin, Jeffrey A.; Kumar, Princy N.; Pauza, C. David; Bordon, José (Frontiers in Medicine, 2022)
The cell and gene therapy product AGT103-T was designed to restore the Gag-specific CD4+ T cell response in persons with chronic HIV disease who are receiving antiretroviral therapy. This autologous, genetically engineered cell product is under investigation in a Phase 1 clinical trial (NCT03215004). Trial participants were conditioned with cyclophosphamide approximately 1 week before receiving a one-time low (< 109 genetically modified CD4+ T cells) or high (≥109 genetically modified CD4+ T cells) dose of AGT103-T, delivering between 2 and 21 million genetically modified cells per kilogram (kg) body weight. There were no serious adverse events (SAEs) and all adverse events (AEs) were mild. Genetically modified AGT103-T cells were detected in most of the participant blood samples collected 6 months after infusion, which was the last scheduled monitoring visit. Peripheral blood mononuclear cells (PBMC) collected after cell product infusion were tested to determine the abundance of Gag-specific T cells as a measure of objective responses to therapy. Gag-specific CD4+ T cells were detected in all treated individuals and were substantially increased by 9 to 300-fold compared to baseline, by 14 days after cell product infusion. Gag-specific CD8+ T cells were increased by 1.7 to 10-fold relative to baseline, by 28 days after cell product infusion. Levels of Gag-specific CD4+ T cells remained high (~2 to 70-fold higher relative to baseline) throughout 3–6 months after infusion. AGT103-T at low or high doses was safe and effective for improving host T cell immunity to HIV. Further studies, including antiretroviral treatment interruption, are warranted to evaluate the product's efficacy in HIV disease. Clinical trial registration www.clinicaltrials.gov, identifier: NCT03215004.